Comparative Analysis of the Recent Financial Crisis' Impact on the Retail Electronic Commerce in the European Union in the USA and in Poland - Czajkowski, Tomasz (Comparative Economic Research. Central and Eastern Europe, 2011)
The aim of this article is to compare and assess the impact of the recent financial crisis on the retail electronic commerce in the economies of the European Union, the USA and Poland. Therefore the selected data from the biggest international companies connected with the retail electronic commerce from the years 2007 and 2008 in comparison to the previous year, and the selected economic data from the economies of the USA, the European Union and Poland till the year 2009, concerning the utilization and value of the electronic commerce trade and the number of people doing shopping online, and conclusions drawn from the analyses of those data are presented and discussed.